CLINICAL ASPECTS OF PATIENT SELECTION FOR CORONARY ANGIOGRAPHY IN NON-ST ELEVATION ACUTE CORONARY SYNDROME - K. A. Kireev (Рациональная фармакотерапия в кардиологии)
Own clinical experience in the selection of patients with non-ST elevation acute coronary syndrome for coronary angiography based on clinical guidelines of the European Society of Cardiology (2011) is presented.